DDIS-16. ONC201 IN COMBINATION WITH RADIATION EXHIBITS SYNERGISTIC EFFICACY IN HIGH GRADE GLIOMAS AND OTHER ADVANCED CANCERS. (5th November 2018) - Tarapore, Rohinton; Jhawar, Sachin; Stein, Mark; Haffty, Bruce; Zloza, Andrew; Mueller, Sabine; Zhang, Jie; Amoroso, Francesca; Mills, Ian; Oster, Wolfgang; Allen, Joshua
Abstract: INTRODUCTION: ONC201 is the first small molecule DRD2 antagonist for oncology that is being investigated as a single agent in advanced cancer clinical trials. Downstream of DRD2 antagonism, ONC201 activates the integrated stress response pathway and apoptosis. ONC201 has exhibited preclinical and clinical anti-tumor activity in high grade gliomas. Given that ONC201 exhibits broad synergy with anti-cancer drugs, excellent safety, and single agent activity in tumor types where radiation is used routinely, we evaluated the combination of ONC201 with radiation in solid tumors. METHODS: Cell viability was evaluated in human and/or mouse breast, prostate and high-grade glioma cell lines in response to ONC201 (1 -10uM), radiation (2– 10Gy), or the combination. Incubation times ranged from 24 to 96 hours and the sequence of the two agents in combination was varied. RESULTS: Cell viability assays for ONC201 in combination with radiation in breast or prostate cancer cell lines revealed a cytotoxic response to the combination than was superior to either single agent. Western blot analysis of PC3 cells showed a synergistic induction of CHOP and ATF6 that are components of the integrated stress response. In MDA-MB-468 cells, Western blot analysis demonstrated a striking induction of PARP cleavage, a marker of caspase-mediated apoptosis, with 2 µM ONC201 in combination with 2 Gy radiation, whereas either single agent produced minimal PARP cleavage. In 4T1 murine triple-negative breast cancer subcutaneous tumors, the combination of oral ONC201 and radiation produced antitumor effects at subtherapeutic doses. In diffuse intrinsic pontine glioma cell lines, combination indices computed from cell viability experiments indicated modest synergy ( 0.7 CI) for the combination ranging between 1–5 µM ONC201 and 2–10 Gy. CONCLUSION: ONC201 combines synergistically with radiation in high grade gliomas and other solid tumors.